2022
DOI: 10.3390/antiox11101872
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Compound Polysaccharides Derived from Astragalus and Glycyrrhiza on Growth Performance, Meat Quality and Antioxidant Function of Broilers Based on Serum Metabolomics and Cecal Microbiota

Abstract: This study aimed to evaluate the effects of dietary supplementation of compound polysaccharides derived from Astragalus and Glycyrrhiza on growth performance, meat quality, antioxidant function, cecal microbiota and serum metabolomics of broilers. A total of 480 one-day-old male Arbor Acres (AA) broilers were randomly divided into four treatments with six replicates comprising 20 broilers each. Treatments: CON group was the basal diet; ANT group was supplemented with Terramycin calcium; LAG group was supplemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 67 publications
0
12
0
Order By: Relevance
“… Pham et al (2023) also found that E. coli O78-challenge increased the abundance of cecum Oscillospira in broilers, which is similar to the results of this experiment. However, Qiao et al (2022a) found that Oscillospira was positively correlated with GPx mRNA expression level, and dietary supplementation of polysaccharides derived from astragalus and glycyrrhiza increased Oscillospira abundance in conventional feeding. We found that Faecalibacterium and Negativibacillus are mainly enriched in E. coli group ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 94%
“… Pham et al (2023) also found that E. coli O78-challenge increased the abundance of cecum Oscillospira in broilers, which is similar to the results of this experiment. However, Qiao et al (2022a) found that Oscillospira was positively correlated with GPx mRNA expression level, and dietary supplementation of polysaccharides derived from astragalus and glycyrrhiza increased Oscillospira abundance in conventional feeding. We found that Faecalibacterium and Negativibacillus are mainly enriched in E. coli group ( Figure 12 ).…”
Section: Discussionmentioning
confidence: 94%
“…On the other hand, shear force and water loss rate are closely related to meat tenderness ( Guo et al, 2022 ). Some studies have found that adding Astragalus and Glycyrrhiza complex polysaccharides could improve broiler meat quality by reducing muscle water loss and shear force ( Qiao et al, 2022 ). In fact, CHAA and CHAB did not enhance the meat’s tenderness, and there was no significant difference in HS group and the CON group in our study ( Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Licorice could improve the meat quality both in broilers and fattening pigs. Flavonoids and triterpene saponins are the main active substances of licorice ( Ahmed et al, 2016 ; Qiao et al, 2022 ) Licorice extract is known to improve immune response by increasing interferon and globulin levels in animals ( Toson et al, 2022 ). Moreover, Poria cocos polysaccharide has also been demonstrated to perform multiple immune effects by promoting antibody production in B lymphocytes and the spleen, increasing serum IgG levels, and enhancing the phagocytosis of macrophages ( Tian et al, 2019 ; Pu et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…To address this challenge, research has shifted towards the investigation of replacing antibiotics with natural bioactive compounds contained in plants. Particularly, some herbal extracts and by-products rich in compounds, mainly polysaccharides, phenols, and flavonoids, such as Astragalus ( Qiao et al, 2022 ) and Acanthopanax senticosus ( Long et al, 2021 ), have attracted much interest and have been utilized to ameliorate the health and growth performance of animals. With this background, we wondered if DOL could also be used as an additive to substitute antibiotics in animal feeds.…”
Section: Introductionmentioning
confidence: 99%